Quantification of dsRNA using stable isotope labeling dilution liquid chromatography/mass spectrometry. (5th March 2018) - Kung, An‐Wen; Kilby, Peter M.; Portwood, David E.; Dickman, Mark J.
Abstract : Rationale: Recent developments in RNA interference (RNAi) have created a need for cost‐effective and large‐scale synthesis of double‐stranded RNA (dsRNA), in conjunction with high‐throughput analytical techniques to fully characterise and accurately quantify dsRNA prior to downstream RNAi applications. Methods: Stable isotope labeled dsRNA was synthesised both in vivo ( 15 N) and in vitro ( 13 C, 15 N‐guanosine‐containing dsRNA) prior to purification and quantification. The stable isotope labeled dsRNA standards were subsequently spiked into total RNA extracted from E. coli engineered to express dsRNA. RNase mass mapping approaches were subsequently performed using liquid chromatography/electrospray ionisation mass spectrometry (LC/ESI‐MS) for both the identification and absolute quantification of the dsRNA using the ratios of the light and heavy oligonucleotide pairs. Results: Absolute quantification was performed based on the resulting light and heavy oligoribonucleotides identified using MS. Using this approach we determined that 624.6 ng/μL and 466.5 ng/μL of dsRNA was present in 80 μL total RNA extracted from 10 8 E. coli cells expressing 765 bp and 401 bp dsRNAs, respectively. Conclusions: Stable isotope labeling of dsRNA in conjunction with MS enabled the characterisation and quantification of dsRNA in complex total RNA mixtures.